Iron Pincer Complexes as Catalysts in Cross-coupling of Aryl Halides and Phenylboronic Acid - Mahesh Kumar, Lolakshi; Ramachandra Bhat, Badekai (International Journal of Engineering and Technology, 2018)
Pincer complexes with iron as active metal center were synthesized to study their catalytic activity in Suzuki-Miyaura coupling reactions. Tridentate pincer ligand was synthesized by the reaction of diphenylchlorophosphine with m-aminophenol and m-phenylenediamine respectively in a 2:1 ratio in the presence of triethylamine as a base and tetrahydrofuran as solvent media. The resultant ligand was complexed with FeSO4 to obtain PCP complexes, C-1 with O and N atoms in the side arms and C-2 with both N atoms in the side arms. The synthesized complexes were examined for their C-C coupling efficiency in cross-coupling between phenyl boronic acid and para substituted halobenzenes. The research study aims to provide an alternative approach to the Pd catalyzed cross coupling methods, an otherwise subjugated method to obtain cross-coupled products. Also the study implores on the effect of variation in the side arm atom relating to the donating ability of the ligand and thereby relatively affecting the coupling yield of the catalysts.Â Â